Effect of wax comb age on Honey bee activity (Apis mellifer meda) - Rashed, Rukhosh; Alan. Krim, Alan. Krim (University of Thi-Qar Journal of agricultural research, 2025)
This study was conducted on Apis mellifera meda hybrid from April to the end of October 2024 including three seasons; spring, summer, and autumn, in the Sulaimani-Kurdistan region. The effect of wax comb age on brood rearing, the activity of workers in honey and pollen storage, and the size of workers’ bodies. Used combs with Foundation as (new comb), and combs aged more than 3 years old as an old comb. The highest average of sealed and unsealed brood areas was 107.363, 62.99 inch2 in the spring season, in the colonies which improved with new combs, the highest average of the honey storage area was 73.706 inch2 in the summer season, the highest average of the pollen storage area was 56.376 inch2 in the spring season in the colonies which improved with new combs. The highest average of the worker’s body length and width was 12.205, 4.348 mm, in the colonies enhanced with new combs. Thus, the results show that regularly replacing aged combs with new ones is useful to improve the activity and productivity of honey bee colonies.